Tracer Study Of Sulphur In The Coke Oven - S. E. Eaton; R. W. Hyde; B. S. Old (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1948)
INTRODUCTION ONE of the most important problems facing the steel industry at the present time is that of maintaining at a minimum the sulphur content of many grades of steel where sulphur is known to have harmful effects on both quality and yield. The present outlook in this struggle to reduce the amount of sulphur in steel is rather gloomy since the sulphur content of the raw materials available in the United States is gradually rising, with little relief in sight. A flow sheet of sulphur in the steel process is shown in Fig I. The values used here were obtained by averaging coke oven and blast furnace data at No. 5 furnace in Cleveland and are considered typical for high top pressure practice. The sulphur evolved in the blast furnace top gas was obtained by difference and since the amount is relatively small, little significance should be attached to this particular value. From Fig I it is apparent, however, that coals used in the production of metallurgical coke represent by far the largest single source of sulphur in steelmaking. As an indication of the decrease in quality of these coals as regards sulphur content the weighed average annual sulphur analysis of the coals supplied to two different steel plants, since 1925, is plotted in Fig 2.1 The sharp rise since 1940 is strikingly apparent. Another indication of this trend is found in estimates of coking coal reserves. Thus in the case of Pittsburgh seam coals available in Allegheny, Fayette, Greene, Washington, and Westmoreland Counties in Pa. as of Jan. 1937 only 25 pct of the coal reserves would contain less than 1.50 pct sulphur after washing.2,3 Many of these lower sulphur reserves have been seriously depleted in recent years because of accelerated war demands. Still another demonstration of the increasing sulphur content of coals on a country-wide basis is found in a report by the Bureau of Mines4 which shows a steady increase in the sulphur content of coke made in the United States, It should be noted that this increase continues in spite of the wider use of coal washing in recent years. Sulphur occurs in coal in three forms, pyritic (FeS2), organic sulphur, and a small amount of sulphate sulphur (CaSO4), The sulphur is subsequently found in the coke in combination with carbonaceous material of unknown composition and as calcium and iron sulphides: In considering the general problem of sulphur elimination, the Republic Steel Corp. was interested in determining which, if either, of the two major forms of sulphur in coal contributes the greater portion of sulphur to the coke, Since the ratio of pyritic to organic sulphur varies widely in different coals, it was thought that if it could be shown definitely that the major part of the sulphur occurring in coke originates from one of the two major forms of sulphur in the coal, it would then be possible to select with confidence coal which, although high in total sulphur, would yield coke of fairly low sulphur content, Using the new